1987
DOI: 10.1111/j.2042-7158.1987.tb03435.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate haemodilution with Fluosol-DA or normal saline on indocyanine green and (+)-propranolol kinetics

Abstract: Indocyanine green (ICG) and (+)-propranolol kinetics were determined in the rat following moderate (50%) blood exchange with either Fluosol-DA or 0.9% NaCl (saline). Rats received an intravenous ICG dose (5 mg kg-1) before an intravenous dose of (+)-propranolol (2.5 mg kg-1) 0.5, 24, 48 or 72 h after haemodilution and were compared with non-exchanged controls. Haemodilution with Fluosol-DA reduced the ICG elimination rate constant during the first 24 h while a significant reduction was seen 48 h after normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Antipyrine absorption was determined in unexchanged rats (control) and rats haemodiluted with 40 mL kg-' Fluosol using a reported procedure (Shrewsbury et al 1987). The antipyrine in-situ intestinal absorption was determined 0.5,24,48 and 72 h after haemodilution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antipyrine absorption was determined in unexchanged rats (control) and rats haemodiluted with 40 mL kg-' Fluosol using a reported procedure (Shrewsbury et al 1987). The antipyrine in-situ intestinal absorption was determined 0.5,24,48 and 72 h after haemodilution.…”
Section: Methodsmentioning
confidence: 99%
“…In these experiments though, indocyanine green was used as the dye reported by Shrewsbury et al(1987) as having a low hepatic extraction ratio in the rat, which led them to study the clearance of (+)-propranolol which has an extraction ratio greater than 0.9. In that study, hepatic blood flow was not altered by moderate haemodilution for 48 h but was significantly decreased at 72 h.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of indocyanine green injected would thus not correspond with the amount detected, and the decreased area under the curve would produce an overestimation of cardiac output. Interestingly, Shrewsbury et al [28] found a decreased indocyanine green clearance during haemodilution with Fluosol-DA or normal saline in the presence of unchanged liver blood flow in rats. They hypothesised that indocyanine green clearance was altered due to changes in its extraction ratio [28].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Shrewsbury et al [28] found a decreased indocyanine green clearance during haemodilution with Fluosol-DA or normal saline in the presence of unchanged liver blood flow in rats. They hypothesised that indocyanine green clearance was altered due to changes in its extraction ratio [28]. However, there have been no further investigations of the influence of haemodilution on indocyanine green clearance and on the detection of indocyanine green concentrations using a finger probe or a nose probe.…”
Section: Discussionmentioning
confidence: 99%